Multivectorality of the Central Asian states in the new geopolitical reality (International relations and international law Journal, 2018)
Phenomenon of the multi vector foreign policy conducted by five Central Asian states Kazakhstan,Uzbekistan, Kyrgyzstan, Tajikistan and Turkmenistan emerged soon after the collapse of the Soviet Unionas a response to plurality of possible directions for development of Central Asia, which for a long historicalperiod served as a bridge connecting South and East Asia with Europe and the Middle East. Thegeopolitical and geostrategic position of Central Asia was the main factor for involvement of leadingworld actors in the region. In this conditions adoption of multi vector foreign policy, which suggestsdevelopment of the progressive and balanced relations with the existing centers of power was the onlypossible variant for Central Asian states to strengthen their sovereignty and independence, gain an impulsefor wide range of domestic reforms and invite investments for further development. Despite thefact that since 1991 have passed more than 25 years and the geopolitical system of relations in CentralAsia has radically changed, the elites of the Central Asian republics realize that maintaining the multivectorforeign policy in the format it was established in the period since independence has become adifficult task under current conditions. Reduction of the US presence in the region, ongoing crisis inUkraine and China’s activation in Central Asian direction transform the geopolitical system of relationsin Central Asia, which loses its flexibility and impedes the effective implementation of a multi-vector foreignpolicy. However, the weakening of some vectors and the parallel strengthening of others does notmean their complete disappearance from the foreign policy palette and the refusal of the Central Asianstates to develop relations with each of the vectors, maintaining multivectorality.Key words: Central Asia, Russia, China, The USA, geopolitics, multi vector foreign policy, narrowingof space, balancing, the Ukranian crisis, the Silk Road Economic Belt